Model keseimbangan umum terapan: Suatu gambaran umum - Y. Sri Susilo (Universitas Islam Indonesia, 1999)
There are many factors that influence economic situation in a country. One of it is an economic policy. The question is how is the impact of an economic policy on economic situation? Some economists believe that in order to answer the question the most significant tool we can use is what we call Applied Computable General Equilibrium Model.